Identification of “bottlenecks” in the systems of adaptability in peach cultivars to specific abiotic factors limiting plant growth and development and affecting individual phases of ontogenesis to develop optimal algorithms for further breeding - I. A. Dragavtseva; V. A. Dragavtsev; A. P. Kuznetsova; A. V. Klyukina (Труды по прикладной ботанике, генетике и селекции)
Modern breeding, especially when fruit plants cultivated for decades at the same location are concerned, requires a new strategy to develop cultivars resistant to abiotic limfactors of the environment. A more in-depth analysis of genotype–environment interaction phenomena is needed, as modern studies have shown that the level of plant productivity and yields is determined not by specific “genes of quantitative traits”, but mainly by the emergent (newly occurring when a lim-factor of the environment changes at the ontogenetic and phytocenotic levels) effects of the genotype–environment interaction (GEI). New knowledge is needed about the values of contributions to the productivity of a cultivar made by each of the genetic–physiological systems of plant adaptability (GPS-ad) when exposed to a particular lim-factor of the environment at a particular phase of ontogenesis. For the first time, aiming at finding promising peach genotypes for further breeding, we studied their adaptability to low temperatures in different horticulture zones of Krasnodar Territory.Shifts in the effects of low-temperature environmental stressors in the developmental phases of cultivars (produced by climate change) were analyzed in the time interval of 1985–2018.The presence of hereditary adaptive reserves for increasing peach productivity for each phase of development in the process of studying the phenomena of GEI was disclosed. Recommendations are given to breeders on phase-to-phase breeding of future cultivars: how to protect their production process at each developmental phase from negative effects of low temperatures.